ASUHAN KEBIDANAN PADA NEONATUS NY “P” DI RUMAH BERSALIN BUNDA PUJA TEMBILAHAN TAHUN 2019 - Dila Okta Viarika; Dewi Erlina Asrita Sari (STIKES HUSADA GEMILANG, 2021)
Neonates care is care that is given to babies until the age of 28 days after birth, the objectives of the midwifery neonates visit care are to examine the newborn, identify symptoms of the disease, and find out as early as possible any abnormalities. The neonatal mortality rate in Indonesia in 2017 as many as 15 cases, in Riau Province 2018 was 393 cases and in Indragiri Hilir Regency was 21 cases. The aim of this midwifery care is to provide midwifery care for the neonate Mrs. “P” at the Bunda Puja Maternity Hospital Tembilahan at 2019 that was using Varney's mindset and documented in the form of a SOAP. The method of data collection was collected using the newborn assesment format from the Academy of Midwifery Husada Gemilang Tembilahan with interviews and observations.. From the results of obstetric care there is a gap in theory and practice, namely the provision of Hepatitis B0 which is not in accordance with the time of giving the neonatal first visit, no SHK examination on the neonatal second visit. It is expected to improve the quality of health services in neonates in accordance with standards and utilize KIA books and for Mother Puja Maternity House is expected to improve the quality of obstetrics services in neonates by paying attention to the provision of Hepatitis B0 according to the delivery time of 0-6 hours, facilitating SHK inspection equipment or conducting cooperation and referral to adequate facilities and utilization of KIA books.